'Nature's offensive': The sociobiological theory and practice of Louis Van der Swaelmen. Issue 3 (2nd September 2019) - Danneels, Koenraad
Abstract: During and after the First World War, Belgian landscape architect and planner Louis Van der Swaelmen attempted to develop a 'sociobiological' theory and practice of landscape architecture, urbanism and urbanization. Both in his writings and designs he combined biological approaches with sociopolitical concerns. In this article, I will focus on the ambitions and ambiguities of this approach. First, a history of ideas will show how the sociobiological theory of Van der Swaelmen was the outcome of an intermingling of the science of ethology and landscape theory. This trajectory culminated in the book Préliminaires d'art civique, in which he created a theory of urbanism based on the idea of urbanization as a process following biological laws, and an urban design approach based on geographical and geobotanical knowledge. The second part of the article will trace the translation of these ideas into the design (process) of the garden suburbs Le Logis and Floréal and will further question the use of a biological approach in urbanism, offering a critical reflection on today's (lack of) sociopolitical questions in ecological urbanism.